ショウワキチ ニオケル タイキチュウ ノ ニサンカタンソ ノウド ノ レンゾク カンソク - 青木, 周司; アオキ, シュウジ; 中澤, 高清; ナカザワ, タカキヨ; Aoki, Shuhji; Nakazawa, Takakiyo (1997)
P(論文) 南極昭和基地(69°00′S, 39°35′E)における大気中のCO_2濃度の連続観測は1984年2月に開始された。昭和基地では, CO_2濃度の日変化は1年を通して全く観測されなかった。CO_2濃度の経年増加率は年々変化しており, 1984年, 1986年, 1988年は増加率が低く, 1985年と1987年は増加率が高かった。特に, 1987年の増加率は他の年に比べて特に大きく, ENSOイベントがその原因になっているものと推定される。過去5年間のCO_2濃度の平均増加率は1.6ppmv yr^<-1>あった。CO_2濃度は平均的には, 4月中旬に最低濃度が出現し, 10月初旬に最高濃度が出現するような季節変化をしており, そのピーク間振幅は1.1ppmvであった。CO_2濃度の実際の季節変化は年々少しずつ変化しているが, 振幅の長期的な拡大傾向は観測されなかった。CO_2濃度には, 数日周期で振幅が0.2ppmv程度の不規則な変化も見られるが, その変化は高低気圧などの総観規模現象によって引き起こされる気団の交代を反映していることが観測から明らかになった。 Precise and continuous measurements of atmospheric CO_2 concentration have been continued at Syowa Station (69°00′S, 39°35′E), Antarctica since February 1984. Diurnal CO_2 variation was hardly observable throughout the year. The secular CO_2 trend was variable with time, showing slow increase in 1984,1986 and 1988 and rapid increase in 1985 and 1987. The annual CO_2 increase was remarkable, especially in 1987,which may have been related to the 1987 ENSO event. The average rate of annual CO_2 increase over the last 5 years was about 1.6ppmv yr^<-1>. The average seasonal CO_2 cycle showed minimum and maximum concentrations in mid-April and in early October, respectively. Its peak-to-peak amplitude was about 1.1ppmv for the period 1984-1988. The seasonal cycle was variable from year to year, but there was no indication of long-term amplitude increase. It was found that irregular CO_2 variations with amplitudes of about 0.2ppmv and with periods of a few tens of days have high correlation with air mass exchange by synoptic scale weather disturbances. departmental bulletin paper